IMPLEMENTASI KEBIJAKAN INDONESIA NATIONAL SINGLE WINDOW (INSW) TERHADAP KEPUASAN EKSPORTIR MEBEL DI PELABUHAN TANJUNG EMAS - Faizal Muhni; Sulistyowati --; Wiwik Widayati (Journal of Politic and Government Studies, 2014)
Indonesia National Single Window (INSW) related to Customsystem, trade, ports and licensing, where Indonesia National SingleWindow (INSW) aims to make the transaction and data processingsystems into one entrance and exit. This system connects and unifiesmany systems into one integrated system.Single Window is a window in the form of ICT (InformationCommunication Technology) is a system that is able to do submissionsof data and information in one submission, the processing of data andinformation and the decision to perform a realease of goods, the realprinciples of the application is that transparency, efficiency, effective,easy and simple.Keywords: Indonesia National Single Window, Customs, Import Export